Misuse of Credit Cards or Carding in Indonesia: How is the Law Enforced? - Fuad, Adib Nor (Law Research Review Quarterly, 2021)
Misuse of credit cards or cards is a negative impact of the times, the advancement of the internet, and the increasingly sophisticated information technology that has resulted in e-commerce activities in countries around the world including Indonesia. Several carding crime cases in Indonesia have troubled many credit card users. This research aims to analyze and examine the criminal law enforcement on misuse of credit cards in Indonesia. This paper highlighted and found that in overcoming crimes in cyberspace, the government issues special regulations for crimes in which the action uses electronic devices and internet networks, namely the Republic of Indonesia Law No. 19 of 2016 concerning amendments to Law of the Republic of Indonesia No. 1 of 2008 which regulates Information and Electronic Transactions or ITE. This regulation aims to suppress carding crimes that are increasingly happening in Indonesia.